(untitled) (American Journal of Islam and Society, 1998)
Since the 1960s, the world has witnessed an increasing fragmentation of the production process across national boundaries; the emergence of transnational (as opposed to multinational) corporations; the rise of new social movements; and heightened cross-border flows of capital and labor. As a result of these developments, scholars and practitioners have sought to understand what has brought about these changes. Is globalization the culprit, or is it simply a myth? If globalization is a reality, what does it entail and how does it affect the realms of economy, polityy and society? In Paul Hirst and Grahame Thompson’s Globalization in Question: The International Economy and the Possibilities of Governance (1 996); James H. Mittelman’s (Ed.) Globalization: Critical Reflections (1 996); and Malcolm Waters’ Globalization (1 999, the struggle to answer these questions and many others is undertaken.’ This article critiques the major points presented by each author in regard to the questions asked above. Each author’s views on globalization as it relates to the economy, the state, and culture will be examined. Furthermore, this article will show that while all three works have their drawbacks and shortcomings, it is recommended that each book be read to gain an understanding of the wide range of empirical and theoretical perspectives on globalization. The conclusion will offer suggestions on areas requiring more in-depth inquiry. What Is Globalization? While Mittelman, as well as Hirst and Thompson, discuss globalization primarily in terms of economic processes, Waters sees globalization as driven by social or cultural processes. According to him, globalization is a “social process in which the constraints of geography on social and cultural arrangements recede and in which people become increasingly aware that they are receding” (p. 3). Waters contends that in a truly ...